NEW HORIZON OF READING ISLAM AND POLITICS: POST-ISLAMISM IN INDONESIA - Noorhaidi Hasan (IN RIGHT: Jurnal Agama dan Hak Azazi Manusia, 2017)
Despite the attempts made by radical Islamists to engulf the political arena of post-Suharto Indonesia by promoting mandatory implementation of shari’a law and jihad, Indonesia has witnessed a new trend in the discourses, actions and movements that seek to push Islam into the center stage. The strategy of implementing the shari‘a from below, promoting da‘wa (Islamic proselytizing) and non-violent endeavors has been appealing and considered more appropriate to deal with the current situations. There is reason to believe that Indonesia today is in the throes of a post-Islamist path. A sort of synthesis between the call for Islam’s importance for public life and democracy, post-Islamism has emerged to be an alternative to Islamist radicalism. Through its endeavour to fuse religiosity and rights, faith and freedom, as well as Islam and liberty, this post-Islamist alternative has enabled Muslims to express their religious beliefs and practices,without plunging into violence and joining a cycle of militancy.